MEMAHAMI ORGANISASI DI LINGKUNGAN PESANTREN - Aziz, Abdullah Aminuddin (Al Tadib : Jurnal Ilmu Pendidikan, 2016)
This article intends to study the organization in boarding schools or pesantren. It is a form of institutionalized Islamic education in Indonesia. The word cottage (rooms, huts, small houses) used in Indonesian with emphasis on the simplicity of building. Conditions boarding school in Indonesia that using dormitories and boarding system, making boarding school populated by a wide variety of origins and character of students. Foundation as an organization that collects collective leadership and control of the existing leadership, has become an alternative to boarding institutions remain viable and survive (survive). However, there are many weaknesses in addition to the advantages of course. Keywords: Pesantren, organization